2016
DOI: 10.1186/s12967-016-1052-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrins β1 and β3 are biomarkers of uterine condition for embryo transfer

Abstract: BackgroundClinical ovulation induction induces blood estrogen (E2) in excess of physiological levels, which can hinder uterine receptivity. In contrast, progesterone produces the opposite clinical effect, suggesting that it might be capable of recovering the lost receptivity resulting from exposure to high estrogen levels. Integrins are the most widely used biological markers for monitoring uterine conditions. We studied progesterone-induced changes in integrin β expression patterns as biomarkers for changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
(21 reference statements)
1
14
0
Order By: Relevance
“…Because Osm could initiate attachment reaction, we would like to analyze how Osm regulated embryo implantation. However, p-Stat3 and integrin b3 are key mediators for mouse implantation [20,21]. Western blot data showed that both p-Stat3 and integrin b3 (Fig.…”
Section: Effect Of Osm On the Implantation Reactionmentioning
confidence: 89%
See 1 more Smart Citation
“…Because Osm could initiate attachment reaction, we would like to analyze how Osm regulated embryo implantation. However, p-Stat3 and integrin b3 are key mediators for mouse implantation [20,21]. Western blot data showed that both p-Stat3 and integrin b3 (Fig.…”
Section: Effect Of Osm On the Implantation Reactionmentioning
confidence: 89%
“…However, p-Stat3 and integrin b3 are key mediators for mouse implantation [20,21]. However, p-Stat3 and integrin b3 are key mediators for mouse implantation [20,21].…”
Section: Effect Of Osm On the Implantation Reactionmentioning
confidence: 99%
“…17,18,27 ITGβ1 is expressed during the menstrual cycle and probably is involved in reconstruction of uterine epithelium after menstruation. 27 Our assessments revealed that the expression level of ITGb1 in RIF patients MB-derived eMSC was lower than that in the cells isolated from non-RIF patients although the difference was not significant (P > 0.05). No related report on the expression levels of ITGb1 in RIF and infertile patients was found in order to compare the obtained data.…”
Section: Discussionmentioning
confidence: 99%
“…Their function is not well known. They have been associated to molecular markers of endometrial receptivity, like integrins, leukemia inhibiting factor (LIF), l-selectin, glutaredoxin, glycodelin-A, microRNAs and, consistently: (i) their development coincides with the implantation window; (ii) the attachment of a blastocyst occurs at the site of pinopode expression in vitro; (iii) the pinopode surface shows receptors for adhesion molecules that are fundamental for embryo attachment to the uterine mucosa [10][11][12][13]. In conclusion, the ultrastructural organization of endometrial cells and the expression of pinopode represent an important part of the complex process of implantation and are crucial steps for adequate placentation at the beginning of pregnancy.…”
Section: Introductionmentioning
confidence: 99%